Pendampingan pengajaran Metode Iqro’ untuk guru-guru di TPA Hayatinnur Tambun Selatan Bekasi - Mia Fitriah Elkarimah; Usman Sutisna (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
The Iqra method is one of the methods in teaching the Qur'an. This method uses the Iqra book, consisting of 6 levels or volumes. Each volume has its difficulties, from volume 1 being the easiest to volume 6 being the most difficult. Many Al-Qur’an Education Parks (TPA) use this method, but in reality, TPA teachers still do not fully understand this Iqra teaching method. Therefore, this PKM aims to identify and improve the quality standards of teaching reading Al-Qur’an using the Iqra method through mentoring activities. Partners in this service come from all teachers and guardians of students at TPA Hayatinnur. This service was held on February 15-16, 2021, at the Hayatinnur TPA hall, attended by four teachers and 24 student guardians divided into two shifts. The method used in this implementation is a direct demonstration or training on the Iqra Method Teaching technique, Class Management, and Classical Iqra Teaching & Problem Solving. After the mentoring was done, it was clear that the teachers had begun to master teaching techniques